Penerapan Game Ular Tangga Berbasis Peta Kebudayaan Untuk meningkatkan Hasil Belajar IPAS Kelas IV Sekolah Dasar - Syalfirah, Vina; Nur Aeni, Ani; Hanifah, Nurdinah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The aim of this research is to find out whether using the snakes and ladders game media based on cultural maps can help improve the cognitive learning outcomes of class IV students in the science and sciences subject on Indonesian cultural riches. The method used in this research is quantitative with a quasi experiment type and a nonequivalent control group design model. There were two sample groups in this study, namely the control class and the experimental class, each class received different treatment. Students in grades IV A and IV B from SDN Sindang IV in North Sumedang District, Sumedang Regency (n=60) were the subjects of this research. According to research results, the snake and ladder game media based on cultural maps can improve students' learning outcomes on Indonesian cultural riches. Learning using this media reaches an N-gain value of 56.03% so it can be categorized as quite effective in improving student learning outcomes, whereas classes that do not use this gaming media only achieve an N-gain value of 36.85% which is considered ineffective. In short, this cultural map-based snakes and ladders game media is superior and quite effective in improving students' cognitive learning outcomes on Indonesian cultural riches material.